Seafloor spreading magnetic anomalies in the Enderby Basin, East Antarctic - Ramana, M.V.; Ramprasad, T.; Desa, M. (Elsevier, 2001)
The timing of the early separation of India from the contiguous Antarctic-Australia is still an unresolved problem although it is well established that Antarctica and India formed a single Indo-Antarctic platform prior to the fragmentation of eastern Gondwanaland. Inadequate age information either in the form of magnetic anomaly isochrons or dating of oceanic rocks from the conjugate margins of Antarctica and India perhaps led several authors to propose incomplete plate reconstruction models particularly for the early separation of India from Antarctica. Analysis of magnetic and satellite-derived gravity data in the Enderby Basin, East Antarctica, reveals the presence of seafloor spreading type linear magnetic anomalies and eight new fracture zones. The observed magnetic anomalies can be interpreted as the younger sequence of Mesozoic anomalies M11-M0. Half-spreading rates range from 6.5 to 2.8 cm/yr and are comparable with those measured in the Bay of Bengal. These similarities in the Mesozoic magnetic anomaly sequence and in the spreading rates provide evidence that these two basins are conjugate and contemporary. A consistent plate reconstruction model can be derived from the identified conjugate patterns of Mesozoic magnetic anomalies and fracture zones. The occurrence of the oldest magnetic anomaly M11 close to the coasts to the coasts in these two offshore basins unequivocally suggests that the break-up of India from Antarctica occurred before approx. 134 Ma